STRATEGIES TO INCREASE EFFICIENCY IN AUDITING PUBLIC SECTOR COMPANIES - Yusupov Ulugbek, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In an era where fiscal transparency and accountability are paramount, the efficiency of public sector auditing plays a critical role in ensuring good governance and sustainable economic management. This paper explores strategic approaches to enhance the efficiency of auditing practices in public sector companies, with a focus on institutional reforms, technological integration, risk-based audit planning, and capacity-building mechanisms. Drawing on international best practices and empirical insights from emerging economies, the study analyses how public audit institutions can modernise their operations to detect financial mismanagement more effectively, reduce audit cycles, and improve the quality of recommendations. Special emphasis is placed on the importance of digital audit tools, the harmonisation of regulatory frameworks, and performance-based audit models. The findings suggest that increasing audit efficiency not only strengthens public financial control but also improves trust in public institutions and resource allocation outcomes. Policy recommendations are proposed to support the strategic transformation of public sector auditing systems, particularly in countries undergoing fiscal modernisation.